Fulfillment Of Safety And Comfort Needs In Urinary Catheter Patients : Literature Review - Agustiani, Sirli; Dewi, Arlina (Universitas Muhammadiyah Yogyakarta, 2020)
Background: Discomfort often occurs when catheter placement and also the removal of catheter. In health sector, nursing practice focus on patient quality and safety. Feeling safe is a form of feeling that if not controlled of anxiety. Using urinary catheter will affect to quality of life of patients such as physical, psychological, socio cultural, environmental and spiritual aspects.Objective: The aims of this study to describe how the fulfillment of safety and comfort needs in urinary catheter patients.Method: This study use literature review. The database were PubMed, Google Scholar and ProQuest. The search was restricted to English language articles and limited to last 5 years (2014-2019). Articles should be related to research. This study use main keywords experience AND â€œurinary catheter*â€. Only fourteen journals met the eligbility criteria and were review by two researchers.Result: The Results of article that urinary catheter impact on several aspect of patients such as social aspect patient have limited social interaction, and difficult to adaptation. In psychological aspect, patient feel embarrassed, dissatisfaction, frustation, anxiety, and low self esteem. In physical aspect, patient feel blocking their movement, increase the risk of infection, painful, discomfort, and iritation. In other aspect, the patient has economic problem.Conclusion: The findings of articles show positive and negative impact for patientâ€™s life when urinary catheter inserted. The review provides insight that can be useful for nurses in concerning patientâ€™s need about safety and comfort especially patients with urinary catheters.